'Roundtable' as a means to an end: Attending to professional and political barriers to sustainable transport - Tiwari, Reena; MacCallum, Diana (University of WA, 2011)
Can Roundtable Discussion be used as a method for understanding and resolving political and professional differences on complex policy issues? It has long been recognised that some policy problems are difficult to address, not only because they are in themselves complex but also because there is no consensus on the issues, information, values or causal relations underlying the problem. Such 'wicked' problems (Rittell and Webber 1973) defy traditional, linear policy analysis; they are thought to require more flexible, deliberative approaches which allow for expression of different meanings and values, and the emergence of new solutions (Healey 2003). One such problem, variously framed by debates on climate change, urban sprawl, economic development and social equity, is the widely acknowledged need to shift to more sustainable patterns of urban transport. With the premise that professional and political differences in the understanding of sustainable transport act as a major impediments towards its implementation, Curtin University organised a roundtable, Moving Cooler - Sustainable Transport Matters, in August 2010. Representatives from the major political parties and relevant government agencies were invited to facilitate discussions for participants from a variety of professions - urban planning, engineering, community development, traffic engineering, urban design, transport planning etc.This paper presents the outcomes from that roundtable, focussing in particular on the following questions: How did the political and professional agendas shape the debate at each table? How effective was the roundtable as a tool for mutual learning and bridging disciplinary and ideological gaps? What aspects of its organisation and management made it effective and/or ineffective? We conclude by offering some ideas about roundtable as a method of collaborative policy analysis in relation to the issue of transport.